PENGARUH OVERCONFIDENCE, EXPERIENCE, EMOTION TERHADAP RISK PERCEPTION DAN RISK ATTITUDE PADA INVESTOR PASAR MODAL DI SURABAYA - Nadia Kartika; Rr. Iramani (Journal of Business & Banking, 2013)
There are some factors which are assumed to have effect on risk perception and risk attitude. This aims study to explain the effect of internal factors on risk perception and risk attitude. The internal factors in this study consist of overconfidence, experience and emotion. The sample was selected from the investors in Surabaya who invested in capital market. The data were collected by means of questionnaires. The questionnaires of surevy respionses weresidtributed to 104 investors in the capital markets of Surabaya. The analysis was done by using Generalized Structured Component Analysis (GSCA) to test hypotheses. The result show that internal factors have no significant effect on risk perception and risk attitude, and neither does risk perception on risk attitude.